1999
DOI: 10.1119/1.880409
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetism in the movies

Abstract: We have developed five introductory electricity and magnetism lessons composed of student activities centering on analysis of short clips from popular movies. We describe our motivation for doing this, the kinds of activities, and offer our materials to those interested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…Based on the findings obtained in the research, it was concluded that the level of scientific realism in the motion-pictures is critically questioned by the conscious audience and that the audience is aware of the role of reality and fiction in the scenes. This general conclusion corresponds to the conclusions reached in the studies within the body of literature (Al-Khalili, 2003;Allday, 2003;Arroio, 2010;Barnett et al, 2006;Brake and Thornton, 2003;Dark, 2005;Everitt and Patterson, 1999;Rogers, 2007;Rose, 2003;Smith, 2009;Taylor, 2003).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Based on the findings obtained in the research, it was concluded that the level of scientific realism in the motion-pictures is critically questioned by the conscious audience and that the audience is aware of the role of reality and fiction in the scenes. This general conclusion corresponds to the conclusions reached in the studies within the body of literature (Al-Khalili, 2003;Allday, 2003;Arroio, 2010;Barnett et al, 2006;Brake and Thornton, 2003;Dark, 2005;Everitt and Patterson, 1999;Rogers, 2007;Rose, 2003;Smith, 2009;Taylor, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Motion picture dimension of informal education has been studied usually through sci-fi movies (Al-Khalili, 2003;Allday, 2003;Arroio, 2010;Barnett et al, 2006;Brake and Thornton, 2003;Dark, 2005;Everitt and Patterson, 1999;Rogers, 2007;Rose, 2003;Smith, 2009;Taylor, 2003). According to Asimov (1968), one of pioneer for using sci-fi as teaching aid, sci-fi stories can be used for illustrating scientific contents and initiating useful discussions between students.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Regarding the above, previous studies have highlighted the effectiveness of using science fiction movies in the classroom to favour student motivation and engagement when it comes to learning science and technology subjects. [12][13][14][15][16][17][18] Specifically, some works have developed projects through which the use of movie scenes has been considered in the classroom for the teaching of Physics. This way, Dennis 19 considered science-fiction movie clips to illustrate physical concepts as a way of supplementing traditional instruction, with such fact resulting in improved motivation from the students as well as better visualization of the fundamentals of Physics.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the use of science fiction movies can be a powerful resource within the lecture room to help students motivate and engage in their learning of different science disciplines (Franknoi, 2002;Rose, 2003;Barnett et al, 2006;Bixler, 2007;Frieden & Elliot, 2007;Blasco et al, 2010;Blasco et al, 2011). Specifically, when it comes to teaching physics or engineering, the use of science fiction movie scenes can represent an interesting complementary methodology to illustrate how (or how not) the laws of physics of our universe behave, while at the same time having fun (Asimov, 1968;Everitt & Patterson, 1999;Chandler, 2002;Daley, 2004;Dark, 2005;Berne & Schummer, 2005). Furthermore, it should be noted that, through science fiction movies, students not familiarized with scientific fields can be stimulated so that new scientific and technological vocations may be awaked (Smith, 2009).…”
Section: Introductionmentioning
confidence: 99%